Analisis Hubungan Antar Organisasi dalam Pengembangan Investasi di Kawasan Perdagangan dan Pelabuhan Bebas Batam - Muzwardi, Ady; Nurmandi, Achmad (Journal of Governance and Public Policy, 2014)
Investment is one source of  state revenue. Until  now the investment management in Indonesia can not be managedoptimally, because one of  them by a system of  investment management organization that is still weak. This study aimedto analyze the relationship between the organization (network governance) in organizing system in the developmentof  investment in the Free Trade Zone and Free Port of  Batam. The method used is the analysis of  network coordina-tion with the study of  the 5 aspects including governance structures, karaketristik service, operational interactionpar tner characteristics and network characteristics on a 3-level organization of provincial and district/city. The analy-sis finds that the coordination between the provincial and district organizations / cities still not optimal. coordinationhorizontally and vertically has not established optimally.